Predictors of exclusive breastfeeding among mothers attending rural health clinics in Hulu Langat district - Mohamad Pilus, Farahana; Ahmad, Norliza; Mohd Zulkefli, Nor Afiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Even though exclusive breastfeeding prevalence has increased from 19.3% in 2006 to 47.1% in 2016, this practice was slightly higher in urban areas (48.3%) compared to rural area (45.1%) in Malaysia. National Plan of Action for Nutrition of Malaysia III has set an indicator to achieve at least 70% exclusive breastfeeding by 2025. Therefore this study is to identify predictors that influenced exclusive breastfeeding practice in rural areas. Methods: This cross-sectional study was conducted in six rural health clinics in Hulu Langat District, Selangor among mothers with youngest child aged 6-48 months old. Respondents were selected through systematic random sampling. Validated self-administered questionnaire was used to assess sociodemographic factors, maternal factors, external factors and child’s factors. Mother’s height and weight was measured and body mass index was calculated. Data were analyzed using SPSS version 23. Multivariate logistic regression was used to determine the predictors for exclusive breastfeeding practice. Results: Response rate was 96% with a total of 311 mothers participated in this study. More than half of the mothers exclusively breastfed (52.4%). The predictors for exclusive breastfeeding were Malay ethnicity (AOR=3.951, 95% CI: 1.374-11.358), having tertiary education (AOR=2.401, 95% CI: 1.100-5.241) and positive attitude toward breastfeeding (AOR=7.755, 95% CI: 1.382-43.502). Conclusion: Prevalence of exclusive breastfeeding was higher in this study than the national level. Programme planners should pay special attention to Chinese and Indian ethnicities, mothers with lower level of education and negative attitude in order to improve breastfeeding practice among rural mothers.